Barbie (2023): The Cultural Icon Redefining Female Empowerment - Zacipa-Infante, Ingrid (2025)
The article examines the movie Barbie (Greta Gerwig, 2023), the highest-grossing film of the year, and its relationship with marketing strategies and gender stereotypes. The objective is to analyze the perpetuation of stereotypes and Mattel's adaptation to gender equality demands through rebranding and campaigns like "You Can Be Anything". The study employs a mixed-methods design, using qualitative and quantitative analysis of the film through co-occurrences and sales data statistics. The main finding is that although the movie presents itself as a phenomenon of female empowerment, it still resorts to traditional stereotypes. The research reveals that the code of female empowerment is recurrent, although patriarchy remains present. The movie's advertising generated a global pink movement that strengthened the audience's emotional connection with the brand but also highlighted tensions between old and new gender representations. The main conclusion is that Mattel has successfully repositioned Barbie as an empowerment icon, though content analysis reveals that the film still struggles with traditional gender representations. The article's primary contribution is the identification of Barbie's successful multichannel marketing strategy and the critical analysis of how this iconic brand attempts to balance tradition and modernity in its gender representation.